Risk Management for the Stability of Islamic Educational Institutions: A Pesantren Case Study in Hidayatul Fauzaniyyah - Fauzi, Muhamad Fikri Halwan; Hanif, Muh. (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2025)
This study investigates how risk management practices contribute to the stability of Islamic educational institutions, using Pesantren Hidayatul Fauzaniyyah as a case study. Employing a descriptive qualitative approach, the research explores institutional efforts in managing operational, financial, human resource, and reputational risks. Data were collected through in-depth interviews, participant observations, and document analysis, with informants selected via purposive sampling. The findings reveal that risk identification is routinely conducted through internal meetings involving school leadership and educators, addressing challenges related to curriculum delivery, financial sustainability, and community engagement. Strategies implemented include the development of income-generating agricultural enterprises, standardized recruitment and training of teaching staff, and structured financial governance. These efforts have strengthened institutional resilience, enhanced educational quality, and fostered community trust. The study highlights the importance of formalizing risk management in pesantren contexts and adapting it to local cultural, religious, and economic settings. While the single-case design limits generalizability, the findings offer a practical framework for other Islamic educational institutions seeking sustainable governance models. Further research should explore comparative and longitudinal case studies to refine context-sensitive risk management approaches in Islamic education.